Swords that are Ploughshares Another Case of (Bilingual) Wordplay in Biblical Prophecy? - Golani, Shira J. (2017)
This paper discusses the image of swords made into ploughshares and spears into pruning hooks, or vice versa, in Isaiah 2,4, Micah 4,3 and Joel 4,10. It advances the suggestion that this image presents a wordplay, most likely a bilingual one, manifested in the choice of specific weapons and agricultural tools to be paired together. This rhetorical device adds a new level of meaning to the prophetic message, enhancing the theme of metamorphosis and reversal of the prophecies in which this image occurs. This case would belong with other examples of bilingual wordplay already acknowledged in the Hebrew Bible.